Strategies for constructing melt-castable energetic materials: A critical review - Qing Ma; Zhenqi Zhang; Wei Yang; Wei Li; Jia Ju; Guijuan Fan (Energetic Materials Frontiers, 2021)
Melt-castable energetic materials are utilized in a wide variety of civilian and military applications, such as construction, demolition, underwater blasting, mining, oil well perforation, and military munitions. 2,4,6-Trinitrotoluene (TNT) is a traditionally-applied melt-castable explosive; however, its low physical-performance output, environmental pollution characteristics, and safety issues restrict its further development towards future industrial applications. This review addresses advances in the design, synthesis, and characterization of new melt-castable energetic materials featuring fluorine, gem-dinitrofluoroethyl, and nitrate ester groups as well as the nitrofurazan and 1,2,4-oxadizaole skeletons, which have led to the development of novel high-performance TNT candidates between 2012 and 2020.